Auxin Is Involved in Magnesium-Mediated Photoprotection in Photosystems of Alfalfa Seedlings Under Aluminum Stress - Su, Liantai; Lv, Aimin; Wen, Wuwu; Zhou, Peng; An, Yuan (Frontiers in Plant Science, 2020)
The objective of this study was to investigate the effects of Mg and IAA on the photosystems of Al-stressed alfalfa (Medicago sativa L). Alfalfa seedlings with or without apical buds were exposed to solutions fully mixed with 0 or 100 μM AlCl3 and 0 or 50 μM MgCl2 followed by foliar spray with water or IAA. Results from seedlings with apical buds showed that application of Mg and IAA either alone or combine greatly alleviated the Al-induced damage on photosystems. The values of photosynthetic rate (Pn), effective quantum yields [Y(I) and Y(II)] and electron transfer rates (ETRI and ETRII), proton motive force (pmf), cyclic electron flow (CEF), proton efflux rate (gH+) and activities of ATP synthase and PM H+-ATPase significantly increased, and proton gradient (ΔpHpmf) between lumen and stroma decreased under Al stress. After removing apical buds of seedlings, the Y(I), Y(II), ETRI, ETRII, pmf and gH+ under exogenous spraying IAA significantly increased, and ΔpHpmf significantly decreased in Mg addition than Al treatment alone, but they were no significant difference under none spraying IAA. The interaction of Mg and IAA directly increased quantum yields and electron transfer rates, and decreased O2- accumulation in Al-stressed seedlings with or without apical buds. These results suggest that IAA involves in Mg alleviation of Al-induced photosystem damage via increasing pmf and PM H+-ATPase activity, and decreasing ΔpHpmf.